Suluh Masyarakat Agama Ramah Lingkungan (Starling): Model Penyuluhan Agama Islam Berwawasan Lingkungan Di Temanggung - Miftachul Huda (Balai Diklat Keagamaan Semarang, 2025)
This research aims to determine the description of the Environmentally Friendly Islamic Religious Extension Model called â€œSuluh Masyarakat Agama Ramah Lingkungan (STARLING)â€ which is used to increase insight and awareness of the importance of preserving the environment among the congregation of the majlis taklim in Temanggung. This research uses a descriptive qualitative approach, data collection uses the document study method, the data analysis method uses the Miles and Huberman method. Namely, after the data is collected, the data is reduced and presented in the form of an Islamic religious education model with an environmental perspective. This model was then tested and revised through discussion and feedback from relevant experts and practitioners. This research succeeded in developing a model of religious counseling called â€œSuluh Masyarakat Agama Ramah Lingkungan (STARLING)â€ which was specifically designed to increase awareness of the importance of preserving the environment among the congregation of the majlis taklim in Temanggung. This model not only focuses on teaching relevant Islamic teachings related to the environment, but also integrates them with practical actions that can be implemented by everyday people.